Concise enantioselective synthesis of (R)-(+)-goniothalamin oxide, a trypanocidal active agent via L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde - Kumar, B. Senthil; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
A short and straight-forward enantioselective synthesis of (R)-(+)-goniothalamin oxide 2 has been achieved with an overall yield of 39% and 99% ee. The synthetic approach involves L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde followed by Lewis acid-mediated diastereoselective allylation of epoxy aldehyde as the key chiral-inducing steps.
Keywords: Allylation; asymmetric epoxidation; Esterification; Grubbs' catalyst; L-prolinol catalyst; Ring closing metathesis